Hubungan Antara Tingkat Nyeri Dengan Kualitas Tidur Pada Pasien Pasca Operasi Apendiktomi di Rumah Sakit Efarina Etaham Berastagi - Destinimawati Halawa; Syafaruddin Saleh Nasution (Politeknik Ganesha Medan, 2025)
Appendectomy is a surgical procedure performed to remove an inflamed appendix caused by appendicitis, one of the most common abdominal surgical cases in hospitals. At Efarina Etaham Hospital in Berastagi, the number of appendectomy procedures has continued to increase in early 2025. Although this procedure effectively treats appendicitis, patients often experience postoperative pain that may disrupt sleep quality. Sleep disturbances resulting from pain have the potential to delay wound healing, decrease immune function, and negatively affect patients’ quality of life. This study aimed to determine the relationship between pain intensity and sleep quality among post-appendectomy patients. A quantitative design with a cross-sectional approach was employed, involving 59 respondents selected through consecutive sampling from a total population of 144 patients. Data were collected using the Numeric Rating Scale (NRS) to assess pain intensity and the Pittsburgh Sleep Quality Index (PSQI) to evaluate sleep quality. Bivariate analysis using the Chi-Square test revealed a p-value of 0.000 (< 0.05), indicating a significant association between pain intensity and sleep quality. The results showed that the majority of respondents experienced moderate (52.5%) and severe pain (33.9%), as well as poor (54.2%) and very poor (33.9%) sleep quality. The study concludes that higher levels of perceived pain are associated with poorer sleep quality. Therefore, effective pain management is essential to improve sleep quality and accelerate postoperative recovery in appendectomy patients.